PRESCHOOL SYSTEM ABROAD: A COMPREHENSIVE OVERVIEW - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article highlights the cornerstone for a child's future intellectual and social success is the preschool years. Although preschool education is available in many nations, there are significant differences in early childhood education's quality and methodology. With links to various nations, we give a thorough overview of the preschool education system overseas in this page.